From 'Sophisticated' to 'Garbage': An Exploration of Qualitative Barriers in the School Educational Technology Infrastructure Maintenance and Procurement Cycle - Ulfatul Munawaroh; Sayidah Eva Milatul Qistiyah; Nur Anim Jauhariyah (STAI AN-NAJAH INDONESIA MANDIRI, 2025)
This study aims to explore the qualitative barriers to infrastructure maintenance and the educational technology procurement cycle in schools, which can lead to devices that were once